2015
DOI: 10.1039/c4ob02393e
|View full text |Cite
|
Sign up to set email alerts
|

The first study about the relationship between the extractability of thiacalix[4]arene derivatives and the position of the coordination binding sites

Abstract: The extractability of thiacalix[4]arene derivatives 2–4 are largely dependent on the position of the binding sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We have previously reported density-functional theory (DFT) computational studies to complement the experimentally observed binding studies. [22][23][24] These DFT studies have also supported the assignment of the likely coordination sites in imidazolyl-and pyridyl-functionalized ionophoric thiacalix [4] arenes.…”
Section: Computational Studymentioning
confidence: 56%
“…We have previously reported density-functional theory (DFT) computational studies to complement the experimentally observed binding studies. [22][23][24] These DFT studies have also supported the assignment of the likely coordination sites in imidazolyl-and pyridyl-functionalized ionophoric thiacalix [4] arenes.…”
Section: Computational Studymentioning
confidence: 56%